Geometric analysis and blood flow simulation of basilar artery - Lee, Sang Hyuk; Hur, Nahmkeon; Jeong, Seul-Ki (Journal of atherosclerosis and thrombosis, 2012)
The aim of this study was to find a region of low wall shear stress (WSS) in a basilar artery using 3-dimensional (3D) geometric analysis and blood flow simulation. A 61-year-old patient who underwent follow-up time-of-flight magnetic resonance angiography (TOF-MRA) of the brain was recruited as the subject of the present study. In the basilar artery, the angle of the directional vector was calculated for the region of low WSS. The subject's 3D arterial geometry and blood flow velocity from a transcranial Doppler examination were used for a blood flow simulation study. The regions of low WSS identified by both geometric analysis and blood flow simulation were compared, and these methods were repeated for the basilar arteries of various geometries from other patients. Two distinct arterial angulations along the basilar artery were identified: lateral and anterior angulations on the anteroposterior and lateral TOF-MR views, respectively. A low WSS region was observed in the distal portion along the inner curvatures of both angulations in the basilar artery. The directional vectors of the region of low WSS calculated by geometric analysis and blood flow simulation were very similar (correlation coefficient= 0.996, p < 0.001). Follow-up MRA confirmed the progression of plaque in the region of low WSS. Detailed geometric analysis and blood flow simulation of the basilar artery identified lateral and anterior angulations which determined the low WSS region in the distal portion along the inner curvatures of the angulations.